IMPLEMENTATION OF GOOD GOVERNANCE PRINCIPLES IN ENHANCING THE PERFORMANCE OF CIVIL SERVANTS AT THE PUBLIC SERVICE MALL (MPP) OF BARRU REGENCY - Asriani; Mahmud, Usamah (P3M Stia Al Gazali Barru and Meraja media, 2024)
[Full Paper] to pdf Copyright (c) 2024 Meraja journal